Detecting trends in bottom pressure measured using a tall mooring and altimetry. Issue 7 (27th July 2015) - Williams, Joanne; Hughes, Chris W.; Tamisiea, Mark E.
Abstract Stable, accurate measurements of ocean bottom pressure would be valuable for a range of purposes, including ocean circulation monitoring and measurement of the mass component of the changing sea level budget. Geographic variability of bottom pressure is in general smaller than variability of sea level, particularly at equatorial sites. However, existing bottom pressure recorder technology suffers from drift of several cm/yr, too much for practical realization of these purposes. Therefore, we investigate the use of a tall hydrographic mooring to detect trends in ocean bottom pressure, using data from the Rapid experiment in the North Atlantic. The accuracy of the method is dependent on the number of instruments on the mooring, and we demonstrate how an ocean model (in our case NEMO) can be used to provide an estimate of accuracy of this technique and hence guide mooring design. We also show how it is also dependent on the operational calibration of instruments. We find that, together with altimetry and sea‐surface temperatures, such a mooring can be used to provide bottom pressure variations to within about 1 mbar (1 cm sea level). We estimate that an optimally calibrated mooring in the North Atlantic could detect a trend in bottom pressure to an accuracy of ±1 mm/yr after approximately 12 years of operation.